2017
DOI: 10.3748/wjg.v23.i24.4399
|View full text |Cite
|
Sign up to set email alerts
|

Para-aortic node involvement is not an independent predictor of survival after resection for pancreatic cancer

Abstract: AIMTo analyze the importance of para-aortic node status in a series of patients who underwent pancreaticoduodenectomy (PD) in a single Institution.METHODSBetween January 2000 and December 2012, 151 patients underwent PD with para-aortic node dissection for pancreatic adenocarcinoma in our Institution. Patients were divided into two groups: patients with negative PALNs (PALNs-), and patients with metastatic PALNs (PALNs+). Pathologic factors, including stage, nodal status, number of positive nodes and lymph nod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 31 publications
(33 reference statements)
2
8
0
Order By: Relevance
“…The survival benefit of completion of the treatment pathway (surgery and chemotherapy) in patients with PDAC is well established and the sequence of chemotherapy is based on preoperative staging (neoadjuvant or adjuvant setting)[ 31 , 32 ]. With regards to PALN involvement, this is further supported by the results of this study as well as others on PALN disease[ 20 , 33 , 34 ]. Therefore, the comparable OS and DFS after completion of the whole treatment, surgery and chemotherapy, suggest that PALN should not be considered as a contraindication for resection if identified intra-operatively.…”
Section: Discussionsupporting
confidence: 91%
“…The survival benefit of completion of the treatment pathway (surgery and chemotherapy) in patients with PDAC is well established and the sequence of chemotherapy is based on preoperative staging (neoadjuvant or adjuvant setting)[ 31 , 32 ]. With regards to PALN involvement, this is further supported by the results of this study as well as others on PALN disease[ 20 , 33 , 34 ]. Therefore, the comparable OS and DFS after completion of the whole treatment, surgery and chemotherapy, suggest that PALN should not be considered as a contraindication for resection if identified intra-operatively.…”
Section: Discussionsupporting
confidence: 91%
“…In PC, the prognostic role of distant metastasis has been well established in various studies [13][14][15]. Nevertheless, the prognostic value of PALN metastasis has not been firmly established [9][10][11]16,17]. When unexpected PALN enlargement is found during curative resection of PC, there is no consensus on whether additional treatment strategies will be implemented.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, Alexandre Doussot reported that frozen sections of PALN yielded accurate PALN assessment 13,[24][25][26] .…”
Section: Discussionmentioning
confidence: 99%